2022
DOI: 10.3389/fmicb.2022.991144
|View full text |Cite
|
Sign up to set email alerts
|

3-Phenyllactic acid generated in medicinal plant extracts fermented with plant-derived lactic acid bacteria inhibits the biofilm synthesis of Aggregatibacter actinomycetemcomitans

Abstract: In the present study, the effect of PLA on a periodontic pathogen, Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans), the biofilm, and virulence-related genes was investigated. We confirmed that two lactic acid bacteria (LAB) strains isolated from plant sources, Lactiplantibacillus plantarum MSC-C2 and Pediococcus pentosaceus K40, secrete PLA into the de Man, Rogosa & Sharpe (MRS) broth when supplemented with phenyl pyruvic acid (PPA) as a precursor to PLA. Moreover, PLA was generated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In summary, CGA influences biofilm formation by interfering with transcription regulators and signaling molecule synthesis (Figure 4e). Several studies have found that the suppressed effects were all involved in the transcriptional inhibition of genes controlling the syntheses and secretions of exopolysaccharides, extracellular proteins and virulence factors [38,39]. This study further confirms that CGA affects the Las, Rhl and Pqs systems.…”
Section: Cga-regulated Qs-related Genessupporting
confidence: 82%
“…In summary, CGA influences biofilm formation by interfering with transcription regulators and signaling molecule synthesis (Figure 4e). Several studies have found that the suppressed effects were all involved in the transcriptional inhibition of genes controlling the syntheses and secretions of exopolysaccharides, extracellular proteins and virulence factors [38,39]. This study further confirms that CGA affects the Las, Rhl and Pqs systems.…”
Section: Cga-regulated Qs-related Genessupporting
confidence: 82%
“…In the common organic acids of the postbiotics and secretions of L. paracasei ET-22, abundant phenyllactic acid was reported to show broad-spectrum inhibition of the biofilm formation of pathogenic bacteria, such as Actinobacillus actinomycetemcomitans , Listeria monocytogenes , Staphylococcus aureus , and Salmonella enteritidis [ 38 ]. Several studies have found that the suppressed effects were all involved in the transcriptional inhibitions of genes controlling the syntheses and secretions of exopolysaccharides, extracellular proteins, and virulence factors [ 39 , 40 , 41 , 42 ]. Another study further confirmed that phenyllactic acid played an inhibitive role on the QS system, including the Rhl and PQS QS systems, to suppress the gene expression of relative virulence-factors and biofilm development [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The optical density values of the semi-quantitative analysis of the biofilm were detected at 570 nm using a microplate reader. To determine biofilm reduction ( Shakya et al., 2022 ), the percentages of biofilm was calculated as follows: (Abs Control represented the group without the addition of drugs). For testing biofilm eradication rates, A. actinomycetemcomitans suspension in the 96-well plate was incubated at 37 ◦ C for 48 hours to form a mature biofilm.…”
Section: Methodsmentioning
confidence: 99%